Thermal Stability of Aqueous Polyurethanes Depending on the Applied Catalysts - Miroljub Barac; Milos B. Rajkovic; Jakov Stamenkovic; Miladin Gligoric; Caslav Lacnjevac; Goran Nikolic; Suzana Cakic (Sensors, 2006)
The thermal stability of aqueous polyurethanes has been measured applying thethermogravimetric analysis. The aqueous polyurethanes (aqPUR) with catalysts of differentselectivity have been studied by use of the dynamic method. To obtain degradations of 0.025,0.05, and 0.10, employing the dynamic method, the heating rates of 0.5, 1, 2, 5, and 10 °Cmin-1 have been used in the range of 30-500 ºC. Using the more selective catalysts in theaqueous polyurethanes, the total resulting time of the decompositon has been on the increaseat all degrees of the degradation and at the particular starting temperature. This paper showsthat the dynamic method based on the thermogravimetric analysis can be used to assess thethermal stability of the aqueous polyurethanes using the catalysts of different selectivity.